Learning from Experiences of Ancient Subak Schemes for Participatory Irrigation System Management in Bali†. (30th March 2017) - Yekti, M.I.; Schultz, B.; Norken, I.N.; Gany, A.H.A.; Hayde, L.
Abstract: Subak irrigation systems have been well known since the ninth century. These systems are managed by a Subak association based on the Tri Hita Karana philosophy, as a faith of Balinese Hindus based on harmony between human beings and God, harmony between people and nature, and harmony between people and people. This philosophy underlies every activity of Subak farmers. To manage Subak systems, Subak associations and farmers pursue the Subak regulation called Awig‐awig Subak as the togetherness consensus that was originally announced by the King and nowadays by the Head of the Regency. As associations for irrigation system management, Subak associations have been already naturally adapted to participatory irrigation management (PIM). This paper has been prepared based on a literature study to portray centuries of experience with ancient Subak irrigation system management, in which PIM was represented by three linked aspects: PIM in irrigation system operation and maintenance; PIM with respect to socioculture and economics of agriculture; PIM in light of a religious community. While several of these systems are now under stress, the results of this literature study may hopefully contribute to sustainable PIM for the operation and maintenance of irrigation schemes in Bali during the forthcoming decades. Copyright © 2017 John Wiley & Sons, Ltd.